2001
DOI: 10.1111/j.1745-6592.2001.tb00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Binary DNAPL Mixtures Using Potassium Permanganate with a Phase Transfer Catalyst

Abstract: Phase transfer catalysts (PTCs) can enhance the oxidation of pure DNAPLs using potassium permanganate by facilitating reactions in the organic phase. This study examined the influence of pentyltriphenylphosphonium bromide (PTPP) as a PTC on the rate of permanganate (MnO4‐) oxidation of DNAPLs in pure phases and mixtures. Kinetic batch experiments with trichloroethylene (TCE), 1,1,2‐trichloroethane (TCA), tetrachloroethylene (PCE), 1,1,2,2‐tetrachloroethane (TECA), and their mixtures, (1:1, v/v) were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Hence, significant attention has been devoted to the investigation of the efficacy of various biological and abiological remediation processes which may accelerate the degradation of chlorinated ethylenes. In particular, remediation of chlorinated ethylenes by oxidation using permanganate has recently been the subject of numerous studies because of the following: oxidation with permanganate is rapid and results in essentially complete mineralization to produce environmentally benign compounds (CO 2 , chloride); permanganate is not scavenged by carbonate or bicarbonate as may be the case with other oxidants; permanganate has a high aqueous solubility in contrast to some other oxidants; permanganate has a long history of use for treatment of drinking water; and remediation using permanganate may be implemented at relatively low cost ( ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, significant attention has been devoted to the investigation of the efficacy of various biological and abiological remediation processes which may accelerate the degradation of chlorinated ethylenes. In particular, remediation of chlorinated ethylenes by oxidation using permanganate has recently been the subject of numerous studies because of the following: oxidation with permanganate is rapid and results in essentially complete mineralization to produce environmentally benign compounds (CO 2 , chloride); permanganate is not scavenged by carbonate or bicarbonate as may be the case with other oxidants; permanganate has a high aqueous solubility in contrast to some other oxidants; permanganate has a long history of use for treatment of drinking water; and remediation using permanganate may be implemented at relatively low cost ( ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of phase-transfer catalyst in an environmental context has only been sparingly studied. Seol and Schwartz [32] and Seol et al [33] found that PTPP paired with MnO 4 − increased the dechlorination rate of TCE and PCE. Experiments by Seol and Schwartz [32] were confined to 60 min batch reactions where Cl − released and MnO 4 − consumed were measured and used to corroborate an improved rate of TCE removal.…”
Section: Discussionmentioning
confidence: 99%
“…The idea for using phase-transfer catalysts would be to allow some of the oxidant (i.e., MnO 4 − ) to partition into the non-aqueous phase DNAPL so that oxidation can occur in both the organic and bulk aqueous phases and reduce the time needed to remove the non-aqueous phase product. Seol and Schwartz [32] and Seol et al [33] used the phase transfer catalyst, pentyltriphenylphosphonium bromide (PTPP) in bench studies and reported increased dechlorination of both TCE and PCE. Although the initial results were promising, reports of using phase-transfer catalysts under transport conditions have not yet been reported.…”
mentioning
confidence: 99%
“…Since its discovery in 1659, potassium permanganate has a long history of application to different fields, such as catalysis, medicine and electrochemical and mechanical areas [12]. It is used as an oxidant in drinking water, wastewater and industrial processes [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. The use of potassium permanganate in the synthesis area was achieved to prepare many manganese oxide nanostructures [29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%